A clinicopathological analysis of 26 patients with infection-associated haemophagocytic lymphohistiocytosis and the importance of bone marrow phagocytosis for the early initiation of immunomodulatory treatment. Issue 1050 (15th December 2012) - Nair, Velu; Das, Satyaranjan; Sharma, Ajay; Sharma, Sanjeevan; Sharma, Prafull; Ray, Sougat; Bhattacharya, Shilajit
Abstract : Objective: To analyse the clinicopathological presentation, outcome and importance of bone marrow haemophagocytosis in patients with infection-associated haemophagocytic lymphohistiocytosis (IA-HLH) in a tertiary care hospital in Northern India. Study design: Between January 2007 and December 2009, 26 consecutive patients meeting the diagnostic criteria for IA-HLH, based on the HLH2004 protocol of the Histiocyte Society, were followed up for between 12 and 34 months (median 20 months). Results: IA-HLH was diagnosed in three of the five patients who died 5–6 weeks after the onset of the illness, whereas diagnosis in the remaining group was made a median of 2 weeks after the onset of the illness. The predominant presenting features were fever (100%), hepatomegaly (69%), splenomegaly (58%) and anaemia (96%). All patients showed >3% haemophagocytosis on bone marrow studies—in four cases after serial aspiration/biopsies. Twenty-one (80.8%) cases were non-fatal and five (19.2%) patients died. The non-fatal cases included eight (38.1%) cases of viral infection, seven (33.3%) bacterial infections, two (9.6%) fungal and four (19.0%) protozoal infections; whereas four (80%) bacterial infections and one (20%) viral infection were associated with the fatal cases. The mean of the nadir blood counts of white blood cells, absolute neutrophil counts and platelets; the mean of all the peak biochemical parameters of liver function tests, lactate dehydrogenase and ferritin and the lowest fibrinogen values before treatment, differed significantly (p<0.05) between the non-fatal and the fatal group, being worse in the latter. Conclusions: IA-HLH is important because it can obscure the typical clinical features of the underlying primary disease, thus delaying the diagnosis and having a negative effect on the outcome. Although bone marrow haemophagocytosis is not a mandatory diagnostic criterion, we found it to be a useful tool together with biochemical parameters for early recognition of HLH, especially in developing countries lacking molecular and flow laboratories. The severity of pancytopenia and derangement in biochemical markers were significantly higher in the patients who died.